Changing eating behaviours to treat childhood obesity in the community using Mandolean: the Community Mandolean randomised controlled trial (ComMando) – a pilot study - Hamilton-Shield, Julian; Goodred, Joanna; Powell, Lesley; Thorn, Joanna; Banks, Jon; Hollinghurst, Sandra; Montgomery, Alan A.; Sharp, Debbie; Turner, Katrina (NIHR Health Technology Assessment Programme, 2014)
Background